SEARCH FOR MINIMUM COST USING TRANSPORTATION Modified DISTRIBUTION - Audry Barbra Kawulusan; Hj. Latifah, SSi., MM Hj. Latifah, SSi., MM (Jurnal Sistem Informasi, 2000)
The need for engineering operations research is needed to solve the problems ofmanagement in taking decisions, especially on the optimal allocation of resourcesresourcesthat are available on the company's operations. problems in allocating a jetof fuel in units of gallons from each vendor to each distribution for the airport shouldbe regulated more effectively and minimize the total transportation cost. thereforeused the modified distribution method for minimizing the total cost of transportation.in the distribution of modified method designed values Ui and vj values with theformula Cij = Ui + vj for all base variables, the calculation of changes in costs (Cij)with Cij = Cij-Ui-VJ for non-base variables, as well as a closed path based on theprocess of stepping stone. with the MODI methods, the authors hope that thesemethods can be one solution to the problem of management to improve efficiency andeffectiveness can.